mHealth Innovation in Asia: Grassroots Challenges and Practical Interventions - Baulch, Emma; Watkins, Jerry; Tariq, Amina (Mobile Communication in Asia: Local Insights, Global Implications, 2018)
mHealth Innovation in Asia; mHealth Initiatives and Policy; Grassroots mHealth Projects in Asia; Practical mHealth Interventions in Asia; Structures and Infrastructures of mHealth in Asia; Mobile Health; Health and Wellbeing; Media and Communications; Development Studies on Public Health; Community Health Workers; Mobile Phones in Health